Pengaruh Paham Keagamaan Terhadap Penerimaan Vaksin Measles Rubella - Alvina Savara Dua Lembang; Puteri Nazwa Amanda Octaviani; Rifqi Adrianor (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2023)
Vaccines are a type of drug that trains the body's immune system, so that it can fight diseases that have never occurred before. Vaccines are designed to prevent disease. This is certainly better, than treating the disease after you have contracted it. Vaccines contain weakened or inactive parts of certain organisms or viruses (antigens) to trigger an immune response in the body. The MR vaccine is a vaccine given to all children aged 9 months to 15 years, to prevent diseases caused by measles and rubella viruses. Measles and rubella are diseases caused by viruses, these diseases are very easy to contract and this virus easily infects people whose immune systems are weak, have never had measles, and have never received a measles vaccine. This virus is transmitted through the respiratory tract through droplets of saliva in the air that come out when a sufferer coughs or sneezes. Children and adults who have never been immunized against measles and rubella are at high risk of contracting these diseases.